AI-DRIVEN TRANSFORMATION OF SUPPLY CHAINS AND LOGISTICS FOR ENHANCED EFFICIENCY AND PROFITABILITY - BILOKON, Tetiana; SHVARTZ, Iryna; HAYDAY, Anastasiia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article explores how artificial intelligence is revolutionizing supply chains and logistics, offering enterprises transformative solutions to drive operational efficiency and enhance profitability. By integrating AI technologies such as predictive analytics, real-time tracking, demand forecasting, and route optimization, businesses can streamline operations, reduce costs, and improve service delivery. The article highlights the substantial financial benefits AI provides, such as reducing inventory costs, enhancing customer satisfaction, and optimizing operational efficiency. Additionally, it examines how AI enables businesses to proactively address disruptions, better manage resources, and respond to market shifts, positioning them for long-term growth and competitive advantage. The article emphasizes that AI is not just a tool for operational enhancement but a critical enabler of strategic business transformation, making it essential for enterprises to adopt AI-driven logistics solutions in an increasingly complex global market.
Keywords: logistics; supply chains; artificial intelligence; efficiency; profitability